2006
DOI: 10.1016/j.bej.2006.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between morphology, rheology and polygalacturonase production by Aspergillus sojae ATCC 20235 in submerged cultures

Abstract: A full factorial statistical design, with the factors of, two taxonomically different strains, seven types of seed culture formulations (slants) and two types of fermentation media were used to investigate the effect of these parameters on the morphology and polygalacturonase production. The rheology of the final fermentation medium was analyzed and appropriate mathematical model was applied to calculate suspension viscosity. It was found that most fermentation broths showed non-Newtonian flow behavior. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
0
30
1
Order By: Relevance
“…This phenomenon was discussed in the previous reports of our group and A. sojae was shown to form pellets in submerged culture under the optimized conditions [19,20,32]; whereas in another study, the same organism formed small mycelial clumps (small groups of entangled mycelia) in the presence of OP and sugar beet syrup as substrates [8]. It is well known that inoculum size is one of the main factors influencing the growth form and product formation in fungal cultures [22,39,40].…”
Section: Effect Of Spore Concentrationmentioning
confidence: 92%
See 2 more Smart Citations
“…This phenomenon was discussed in the previous reports of our group and A. sojae was shown to form pellets in submerged culture under the optimized conditions [19,20,32]; whereas in another study, the same organism formed small mycelial clumps (small groups of entangled mycelia) in the presence of OP and sugar beet syrup as substrates [8]. It is well known that inoculum size is one of the main factors influencing the growth form and product formation in fungal cultures [22,39,40].…”
Section: Effect Of Spore Concentrationmentioning
confidence: 92%
“…Due to the high viscosity, higher agitation rates, more power is required to attain desired mixing and oxygen transfer [25]. Pellet morphology has the advantage of exhibiting non-viscous broth with Newtonian behavior, so that better mixing and aeration can be provided and also separation of biomass from the broth is simpler [19]. However, the interior of the pellets based on it compactness degree can be sometimes nutrient and oxygen limited, where growth and product synthesis are impaired [24,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated already the potential of pectinase production by Aspergillus sojae in both fermentation systems (Gögus et al 2006;Heerd et al 2012;Ustok et al 2007). Moreover, providing selected PG overproducing mutants, which were generated by the work described herein, for fermentation process parameter optimization studies focusing on PG titers, demonstrated the successful process development in submerged or solid-state culture (Buyukkileci et al 2011;Demir et al 2012).…”
Section: Introductionmentioning
confidence: 90%
“…In our previous study [17], it was demonstrated that this organism held a considerable potential for the production of the polygalacturonase enzyme. In the corresponding study it was shown that, if this organism was subcultured in molasses agar seed media and grown in complex growth media agitated at 250 rpm at 30 • C, it would exhibit a pellet morphology that is of great interest to large scale submerged fermentations due to easier downstream processing.…”
Section: Introductionmentioning
confidence: 99%